MRI Dynamically Evaluates the Therapeutic Effect of Recombinant Human MANF on Ischemia/Reperfusion Injury in Rats - Wang, Xian-Yun (Int J Mol Sci, 2016)
As an endoplasmic reticulum (ER) stress-inducible protein, mesencephalic astrocyte-derived neurotrophic factor (MANF) has been proven to protect dopaminergic neurons and nondopaminergic cells. Our previous studies had shown that MANF protected against ischemia/reperfusion injury. Here, we developed a magnetic resonance imaging (MRI) technology to dynamically evaluate the therapeutic effects of MANF on ischemia/reperfusion injury. We established a rat focal ischemic model by using middle cerebral artery occlusion (MCAO). MRI was performed to investigate the dynamics of lesion formation. MANF protein was injected into the right lateral ventricle at 3 h after reperfusion following MCAO for 90 min, when the obvious lesion firstly appeared according to MRI investigation. T2-weighted imaging for evaluating the therapeutic effects of MANF protein was performed in ischemia/reperfusion injury rats on Days 1, 2, 3, 5, and 7 post-reperfusion combined with histology methods. The results indicated that the administration of MANF protein at the early stage after ischemia/reperfusion injury decreased the mortality, improved the neurological function, reduced the cerebral infarct volume, and alleviated the brain tissue injury. The findings collected from MRI are consistent with the morphological and pathological changes, which suggest that MRI is a useful technology for evaluating the therapeutic effects of drugs.